Additional Pelagornithidae remains from Seymour Island, Antarctica - Acosta Hospitaleche, Carolina Ileana Alicia; Reguero, Marcelo Alfredo (Journal of South American Earth Sciences)
Two incomplete mandibles are assigned to Pelagornithidae given the presence of a well marked neurovascular furrow and the unique bony projections, or “pseudo-teeth”, along the crista tomialis. Specimens IAA-Pv 175 from Ypresian levels of La Meseta Alloformation (Cucullaea I Allomember), and IAA-Pv 823 from Bartonian beds of the Submeseta Alloformation, in Seymour Island (Antarctic Peninsula, West Antarctica) corresponds to the morpho-type 1, previously proposed for Antarctic pseudo-tooth birds. The intermediate condition of the pseudo-teeth of these specimens reinforces the idea that diet changed from piscivory to molluscivory along the evolutive history of the group. Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Reguero, Marcelo Alfredo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina